2017
DOI: 10.1139/apnm-2016-0518
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the exercise intensity that elicits maximal fat oxidation in individuals with obesity

Abstract: Maximal fat oxidation (MFO) and the exercise intensity that elicits MFO (Fat) are commonly determined by indirect calorimetry during graded exercise tests in both obese and normal-weight individuals. However, no protocol has been validated in individuals with obesity. Thus, the aims were to develop a graded exercise protocol for determination of Fat in individuals with obesity, and to test validity and inter-method reliability. Fat oxidation was assessed over a range of exercise intensities in 16 individuals (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
4
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(55 citation statements)
references
References 31 publications
4
46
4
1
Order By: Relevance
“…Regarding the graded incremental exercise test, even if cycle ergometer has been more often used for CPET tests in obese subjects, we chose the treadmill because it reflects better the walking exercise that subjects might perform as regular unsupervised PA in an almost daily routine. Our MFO results were higher than those reported by other studies in obese subjects (MFO ranging from 0.25 to 0.4 g/min) [9,35]. These differences might by justified by the different graded exercise protocol, and nutritional status of the subjects during the experimental test.…”
Section: Salivary Cortisol Levelscontrasting
confidence: 87%
“…Regarding the graded incremental exercise test, even if cycle ergometer has been more often used for CPET tests in obese subjects, we chose the treadmill because it reflects better the walking exercise that subjects might perform as regular unsupervised PA in an almost daily routine. Our MFO results were higher than those reported by other studies in obese subjects (MFO ranging from 0.25 to 0.4 g/min) [9,35]. These differences might by justified by the different graded exercise protocol, and nutritional status of the subjects during the experimental test.…”
Section: Salivary Cortisol Levelscontrasting
confidence: 87%
“…We recognize this clear limitation of our study. However, adding 1 extra minute to each stage would have extended the total duration of the protocol by 5-6 min, which in these subjects could also have affected VO2 and VCO2, especially at the last steps [37]. Future studies should be performed to analyze the impact of the stages length of exercise test on substrate oxidation in obese individuals with different grades of metabolic health.…”
Section: Discussionmentioning
confidence: 99%
“…The first reliability study of the Fat max protocol described above reported a coefficient of variation (CV) of 9.6% for Fat max in a cohort of overnight fasted moderately-trained males with 24-h pre-trial dietary repetition (Achten and Jeukendrup, 2003a ). Interestingly, a similar study reported a CV of just 3% for Fat max and 11% for MFO (Dandanell et al, 2017b ). These CVs are similar to those for MFO measured in sedentary cohorts using 4–5 pre-defined submaximal workloads based on prior assessment of maximal aerobic power (Gmada et al, 2012 ; Marzouki et al, 2014 ).…”
Section: Exercise Intensity and Whole-body Fat Oxidationmentioning
confidence: 91%